Analysis of the relationship between the degree of economic freedom and foreign trade of selected developing countries for the period (1990-2005) * - خضير, ايمان عبد; خدر, سردار عثمان (Journal of Economics and Administrative Sciences, 2012)
Is a high degree of economic freedom an important part in the development of the economies of developing countries in the last decade of the twentieth century and the beginning of the twentieth century and the atheist. This is because a test subject (deltoid analysis of the relationship between the degree of economic freedom and foreign trade of selected developing countries for the period ( 1990 -2005) to determine the degree of economic freedom in foreign trade promotion in Singapore and Turkey. The research recommends a number of  recommendations, the most important is the responsibility of the Ministry of Planning in Iraq that is providing the necessary data for the Fraser Institute, the aim of increasing cooperation on the export of degrees of freedom and economic indicators and categorized in Iraq.